2016
DOI: 10.1245/s10434-016-5661-x
|View full text |Cite
|
Sign up to set email alerts
|

Survival Analysis and Risk for Progression of Intraductal Papillary Mucinous Neoplasia of the Pancreas (IPMN) Under Surveillance: A Single-Institution Experience

Abstract: PurposeWhile surveillance of the majority of patients with IPMN is considered best practice, consensus regarding the duration of follow-up is lacking. This study assessed the survival rate and risk for progression of IPMN under surveillance.MethodsAll patients diagnosed with and surveyed for IPMN between January 2008 and December 2013 were identified and assigned to two groups: patients without indication for surgery (Group 1), and patients whose IPMN required surgery but were inoperable for general reasons (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
63
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 24 publications
9
63
0
7
Order By: Relevance
“…Patients with high‐risk stigmata also had decreased DSS, whereas worrisome features and the diagnosis of IPMN without risk factors were not associated with mortality independent of the degree of dysplasia, unless invasive IPMN occurred. This supports previous reports of the low risk of progression of IPMN with worrisome features, but higher mortality, in patients with high‐risk stigmata under surveillance.…”
Section: Discussionsupporting
confidence: 91%
“…Patients with high‐risk stigmata also had decreased DSS, whereas worrisome features and the diagnosis of IPMN without risk factors were not associated with mortality independent of the degree of dysplasia, unless invasive IPMN occurred. This supports previous reports of the low risk of progression of IPMN with worrisome features, but higher mortality, in patients with high‐risk stigmata under surveillance.…”
Section: Discussionsupporting
confidence: 91%
“…In 2015, a meta‐analysis was published including 2177 patients under surveillance for SB‐IPMN, of which only 82 (3.7%) developed a pancreatic malignancy . Since then, several additional studies, each including at least 300 patients with at least 5 years of follow‐up, reported a pancreatic cancer risk of only 0%‐1.6% for small asymptomatic cysts . However, all these studies were retrospective and the actual, long‐term risk is yet to be determined by large and prospective studies.…”
Section: Introductionmentioning
confidence: 99%
“…In BD IPMNs, imaging surveillance is reasonable in asymptomatic patients (without obstructive jaundice, diabetes or acute pancreatitis) with lesions smaller than 4 cm, and without high risk stigmata (mural nodules, more than 6 mm dilatation of the MD or cytological atypia). Additionally, elevated serum carbohydrate antigen (CA) 19.9 levels or a growth rate of more than 2mm/year, are relative risk factors that should be considered in the evaluation of these patients (4,7,10). Applying the European guidelines to our patients, the 7 patients with adenocarcinoma would have undergone surgical resection, but 1 of the 4 tumors with highgrade dysplasia would not be resected (table 3).…”
Section: Discussion Discussionmentioning
confidence: 99%